2017
DOI: 10.1186/s12891-017-1562-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between disc space narrowing, anterior osteophytes and disability in chronic mechanical low back pain: a cross sectional study

Abstract: BackgroundRadiographic features of lumbar disc degeneration (LDD) are common findings in patients with chronic mechanical low back pain; however, its role in disability and intensity of pain is debatable. This study aims to investigate the associations of the x-ray features of LDD and lumbar spondylolisthesis with severity of disability and intensity of pain.MethodsA cross-sectional study was conducted on 439 patients with chronic mechanical low back pain who attended the rheumatology clinic, National Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
2
20
3
Order By: Relevance
“…Most of these studies are done as population based studies and restricted to middle aged/elderly individuals or one gender. In contrast, clinic based studies have failed to identify a significant association between the x-ray features of LDD and intensity of LBP or disability [29,41,42].…”
Section: Role Of Radiological Features Of Lumbar Disc Degeneration Inmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of these studies are done as population based studies and restricted to middle aged/elderly individuals or one gender. In contrast, clinic based studies have failed to identify a significant association between the x-ray features of LDD and intensity of LBP or disability [29,41,42].…”
Section: Role Of Radiological Features Of Lumbar Disc Degeneration Inmentioning
confidence: 97%
“…The imbalance between the degradation and inhibitory pathways is also increased with disc degeneration [27,28]. Our recent cross sectional study done in Sri Lanka reported that advanced degenerative features of the spine were present in younger patients (20-29 years) with chronic LBP raising the question that LDD may not be entirely age related [29].…”
Section: Lumbar Disc Degeneration and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors' information (optional) 1 Department of Spine Surgery, Qingdao west coast new area central hospital of Binzhou medical college, Qingdao, China…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Intervertebral disc degeneration (IDD) is strongly associated with low back pain (LBP) [1,2], which accounts for about $100 billion in annual medical expenditure lost wages, and decreased productivity in the of the United States [3]. Degeneration of the disc is usually attributed to aging ageing, genetic, mechanical, and nutritional factors, the environment and individual which is characterized by a decrease in proteoglycans, cell population, water content, and loss of disc height [4].…”
Section: Introductionmentioning
confidence: 99%